Analisis Kualitas Layanan Opac Terhadap Kepuasan Pengguna Menggunakan Metode Servqual Perpustakaan UIN STS Jambi - Padila, Siti; Setiawan Assegaff; Fachruddin (LPPM Universitas Dinamika Bangsa, 2025)
The library is an excellent place to obtain accurate information, whether to enhance knowledge, facilitate the search for materials and academic assignments, or even serve as a resource for creating scientific works. OPAC (Online Public Access Catalog) is an information retrieval tool that library users can utilize to access and search for library collections they need. This system is designed to help library visitors quickly and accurately find the reading materials they require. Based on observations and interviews conducted, it was found that some collections listed in OPAC are not available on the library shelves when searched. Additionally, some students still struggle to understand the book coding listed in OPAC. Referring to these issues, the author aims to analyze the service quality of OPAC in relation to user satisfaction using the SERVQUAL method, which includes five variables: tangible, reliability, responsiveness, assurance, and empathy. The purpose of this research is to analyze the service quality of the Online Public Access Catalog (OPAC) concerning user satisfaction at the Library of Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. Additionally, it seeks to provide information regarding user satisfaction with OPAC by examining the SERVQUAL dimensions in the library. The data analysis is processed using the SEM method with SmartPLS software. The results of the analysis, based on hypothesis testing, reveal that the tangible and reliability variables significantly affect user satisfaction. However, the responsiveness, assurance, and empathy variables do not significantly influence user satisfaction.